Enhancing adherence, subjective well-being and quality of life in patients with schizophrenia: which role for long-acting risperidone?. (October 2015) - Niolu, Cinzia; Bianciardi, Emanuela; Di Lorenzo, Giorgio; Marchetta, Claudia; Barone, Ylenia; Sterbini, Nicoletta; Ribolsi, Michele; Reggiardo, Giorgio; Siracusano, Alberto
Aim: This study evaluated adherence to treatment, quality of life and subjective well-being in patients with psychosis treated with long-acting injectable risperidone. Subjects enrolled were part of a larger study where patients were observed in an adherence to treatment program of the University of Rome Tor Vergata. Materials and methods: A total of 27 nonadherent patients (21 men, six women; mean age: 36.1 years; range: 23–63 years) were enrolled. Maximum observational period was 30 months. Results: A total of 12 patients were under treatment for 30 months (44.44%) but only nine had a valid 30-month follow up, while the remaining three patients initially treated at our unit continued long-acting risperidone at their local centre. Reductions of monthly mean values of Scale for the Assessment of Positive Symptoms (SAPS) [repeated measures analysis of variance (rm-ANOVA): p < 0.0001] and Scale for Assessment of Negative Symptoms (SANS) ( p < 0.0001), increase of monthly mean values of Subjective Well-Being Under Neuroleptic Treatment Scale (SWN) ( p < 0.0001) and Schizophrenia Quality of Life Scale (S-QoL) ( p < 0.01) were observed. Significant differences with respect to SAPS baseline values from the sixth month, SANS baseline values from the seventh month, SWN baseline values from the eighth month, S-QoL baseline values from the eighteenth month were shown in post hoc tests. Reduction of SAPS mean values was associated with increase of SWN ( p < 0.0001) and S-QoL ( p < 0.0001) mean values as demonstrated by correlation analysis. The same inverse correlation was found between reduction of SANS mean values and increases of SWN ( p < 0.0001) and S-QoL ( p = 0.0001) mean values. Conclusions: Long-term treatment with long-acting risperidone may be associated with improvement to adherence to therapy and quality of life. Patients may show improvement in psychopathological symptoms, subjective well-being and quality of life.